2020
DOI: 10.1002/ehf2.13088
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial dysfunction and C‐reactive protein predict the incidence of heart failure in hypertensive patients

Abstract: Aims Endothelial dysfunction and heart failure are associated, but no prospective studies demonstrated that impaired endothelium‐dependent vasodilation predicts incident heart failure. We designed this study to test whether endothelial dysfunction is associated with incident heart failure in a group of hypertensives. Methods and results We enrolled 735 White never‐treated hypertensive outpatients free from heart failure, diabetes, chronic kidney disease, and previous cardiovascular events. Endothelium‐dependen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
21
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 35 publications
2
21
0
1
Order By: Relevance
“…hsCRP levels have been reported as independent prognostic determinants in NIDCM and generally increase as HF progresses. 3,[23][24][25] Myocardial fibrosis is also a prognostic determinant. 5,6 However, hsCRP and CVF were not significant determinants in our results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…hsCRP levels have been reported as independent prognostic determinants in NIDCM and generally increase as HF progresses. 3,[23][24][25] Myocardial fibrosis is also a prognostic determinant. 5,6 However, hsCRP and CVF were not significant determinants in our results.…”
Section: Discussionmentioning
confidence: 99%
“…15,28,29 The relationship between vascular endothelial function and HF has also been reported. 23,30 Elevated ATX might also increase the levels of other inflammatory substances, which might have affected the prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…NPTX2 encodes a synaptic protein associated with C-reactive protein. Several studies have confirmed that C-reactive protein can effectively predict the occurrence of HF ( Maio et al, 2021 ). Deletion or mutation of BLM may result in telomere defects and accelerated telomere shortening ( Callén and Surrallés, 2004 ).…”
Section: Discussionmentioning
confidence: 98%
“…Additionally, hs-CRP is a marker of senescence and aging, which is characterized by the accumulation of senescent cells that release proinflammatory cytokines, chemokines and other mediators that lead to inflammatory microenvironments in many tissues and organs ( Bruserud et al, 2022 ). Moreover, CRP level is correlated to the endothelial dysfunction and may reflect the development of atherosclerosis ( Della Corte et al, 2016 ; Maio et al, 2021 ). These evidences can explain the correlation between CRP and risk of cardiovascular and malignancy related morbidity and mortality.…”
Section: Discussionmentioning
confidence: 99%